(untitled) (Scientific Journal of Research Studies in Future Psychology, 2024)
This study aimed to stuy the effectiveness the reality therapy on hypertension, functional flexibility and aggression of spouses of people with a addition of substance abuse Residence centers. research on semi-experimental project and statistical population of the study included the spouses of people with a history of substance abuse in addiction treatment centers between the ages of 40-40,whose spouses lived in addiction treatment centers in shiraz in 1399.to conduct research, 30 spouses of people with a history of substance abuse in selected addiction treatment in shiraz all selected, who are randomly assigned to two experimental and control groups. the two groups were matched in terms of demographic characteristics. the research measurement tools were HS synder (HS),aggression Qutstionnaire (AGQ)and flexibility Qutstionnaire (CFI).the results of data analysis using one-variable and multivariate analysis of variance showed that reality therapy had a significant effect on the well-being of spouses of people with a history substance abuse in addiction treatment centers the ages of 40-40 reality therapy also had a significant effect on the functional flexibility of the spouses of people with a history of substance abuse in addiction treatment centers between the ages of 40 and 30. according to other results of reality therapy, the aggression of the spouses of people with a history of substance abuse in addiction treatment centers between the ages of 40 and 30 had a significant effect.